Analysis of Factors Influencing to The Incidence of Hypertension In Patients of Hospitalized In Hospital Nacional Guido Valadares (HNGV), Timor Leste - Pinto, Joaquim; dos Santos, Hermina; do Rosario de Jesus Leite, Ana; de Jesus, Acacio; Belo, Gregorio; Soares, Miguel (Riviera Publishing, 2022)
Introduction:this study were hypertensive patients hospitalized at HNGV, internally male and female, with a total of 32 populations. The sample used was a non-probability sampling technique with a purposive sampling technique. The research instrument uses validity and reliability tests. Result: Based on research conducted on male and female HNGV internal customers, smoking behavior factors positively affect the incidence of hypertension. This is indicated by a significance test value of 0.041, which is less than 0.05, the alcohol consumption factor also has a positive effect on the incidence of hypertension with a significance test value of 0.022, which is less than 0.05, and the stress factor also has a positive effect. Effect on the incidence of hypertension with a significance test value of 0.041, which is smaller than 0.05. Conclusion: There is an influence between smoking behavior, alcohol consumption and stress on the incidence of hypertension in internal and internal HNGV women.